Business Analytics as a Strategic Resource for Innovation: A Comprehensive Review - Juwari; Marthalia, Lia; Widayat, Tri Agung; Andrianto, Deny Tomy (Novatio : Journal of Management Technology and Innovation, 2024)
This study provides a narrative review of the role of business analytics in driving organizational innovation performance. The purpose is to synthesize current empirical and theoretical contributions with a focus on organizational capabilities, market dynamics, leadership, culture, and global perspectives. Literature was identified through major databases (Scopus, Web of Science, PubMed, and IEEE Xplore) with inclusion criteria emphasizing peer-reviewed studies from the last decade. Findings highlight four key insights: organizational capabilities mediate the translation of analytics into innovation; market dynamism moderates its effectiveness; leadership and culture are decisive in embedding analytics; and adoption disparities persist between developed and developing economies. The review concludes that business analytics strengthens strategic agility and sustainable competitiveness, though barriers such as data quality, infrastructure, and ethics remain. Future research should explore longitudinal impacts, small and medium enterprises, and cross-country comparisons to optimize analytics-driven innovation.